The Road to a Digitalized Supply Chain Management: Smart and Digital Solutions for Supply Chain Management - Wolfgang Kersten; Thorsten Blecker; Christian M. Ringle (epubli GmbH, 2018)
This volume contains research contributions by an international group of authors addressing innovative and technology-based approaches for logistics and supply chains. They present business models and investment options for enhanced strategic decision making as well as recent approaches for supply chain analytics and risk management. This volume, edited by Wolfgang Kersten, Thorsten Blecker and Christian Ringle, provides valuable insights into the digitalization of Supply Chain Management and Logistics with regard to: Innovation and Technology Management, Advanced Manufacturing and Industry 4.0. Supply Chain Analytics, Risk and Security Management.
urn:nbn:de:gbv:830-88223093; https://econpapers.repec.org/RePEc:zbw:hiclch:209340; https://econpapers.repec.org/RePEc:zbw:hiclch:209341; https://econpapers.repec.org/RePEc:zbw:hiclch:209342; https://econpapers.repec.org/RePEc:zbw:hiclch:209343; https://econpapers.repec.org/RePEc:zbw:hiclch:209344; https://econpapers.repec.org/RePEc:zbw:hiclch:209345; https://econpapers.repec.org/RePEc:zbw:hiclch:209346; https://econpapers.repec.org/RePEc:zbw:hiclch:209347; https://econpapers.repec.org/RePEc:zbw:hiclch:209348; https://econpapers.repec.org/RePEc:zbw:hiclch:209349; https://econpapers.repec.org/RePEc:zbw:hiclch:209350; https://econpapers.repec.org/RePEc:zbw:hiclch:209351; https://econpapers.repec.org/RePEc:zbw:hiclch:209352; https://econpapers.repec.org/RePEc:zbw:hiclch:209353; https://econpapers.repec.org/RePEc:zbw:hiclch:209354; https://econpapers.repec.org/RePEc:zbw:hiclch:209355
Keywords: 650; Supply Chain Management; Logistics; Digitalization; Supply Chain Risk Management; Industry 4.0; Lieferkette; Logistik; Digitalisierung; Risikomanagement; Industrie 4.0